Strength abilities characteristics of elite Rugby Union 15 players - Pietranis, Dariusz; Janowski, Jarosław; Karpowicz, Krzysztof (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The purpose of this paper was to analyse the level of motor abilities in terms of strength abilities among the players of premier league for rugby union in Poland as well as defining the relationship between the level of the strength abilities and the sports level of the team.Research material covered 79 players from three teams representing differential sports level which were selected from the Polish rugby premier league. The research included performing antropometric measurements, barbell squat maximal force and power output measurements, having been conducted with the use of Tendo Weightlifting Analyser.It was indicated that the teams placed higher in the premier league were the ones with higher mean body mass of the players, which could have contributed to their scoring higher also in strength ability tests. Moreover, it was confirmed that the forwards have significantly higher body mass than the backs.It appears that the most significant element in training rugby players is the possibility of obtaining high maximal power output of lower limbs, in its both, relative and non-relative aspect as well as force understood in the same context (relative and non-relative one).